Expression of gonadotropin-releasing hormone receptor type-II correlates with proliferation activity in tissue microarray of rare ovarian tumor - Kiky Martha Ariesaka; Ardhanu Kusumanto; Muhammad Ary Zucha; Nungki Anggorowati; Agil Wahyu Wicaksono; Moch Yunus; Erianto Fanani; Moh Mirza Nuryady (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2024)
Activation of Gonadotropin-Releasing Hormone type II Receptors (GnRHR-II) exhibits antiproliferative activity. GnRHR-II is not only expressed exclusively in the pituitary, but also in a variety of tumors. To date, the clinical relevance of GnRHR-II in ovarian tumors is unclear. In addition, there is a lack of literature addressing GnRHR-II in ovarian tumors, especially rare types. This study was conducted to investigare the correlation between GnRHR-II expression with clinicopathology and proliferative activity of rare ovarian tumors. The purpose of this study was an analytic observational study with a cross-sectional design that utilized 18 ovarian tumor samples on tissue microarray (TMA). The expression of GnRHR-II and Ki67 was assessed using immunohistochemical staining (IHC) and observed using the IHC profiler plugin ImageJ software to obtain their respective H-scores. The data was analyzed using independent t-test, ANOVA, Pearson's test, and Fisher's exact test based on data types. The value of p<0.05 was considered statistically significant. GnRHR-II is expressed in various forms in ovarian tumors, including extrapituitary expression. GnRHR-II expression was highest in the sex cord stromal tumor (SCST) group, 110.30 ± 23.89 (p<0.0001). In addition, there was also a significant difference between GnRHR-II expression with age (p<0.001) and the primary tumor (p<0.05), but not with tumor type (p=0.101). There is a correlation between GnRHR-II expression and proliferative activity (r=-0.043, p=0.866). Elevated GnRHR-II expression is significantly correlation with SCST, individuals over 40 years of age, and tumors confined to the ovary and it is correlates with lower proliferative activity, although this correlation is very weak.